Un esbozo de solución a un enigma de Kripke - Raúl Orayen (Crítica)
The principle of substitutivity of identicals yields well-known paradoxes, when applied to epistemic contexts. In “A Puzzle about Belief”, Kripke has tried to show that similar paradoxes arise without any use of the above mentioned principle. This paper analizes the main paradox involved in Kripke’s article and tries to give a solution to it based on Kripke’s theory of proper names as presented in Naming and Necessity.